Delmar's critical care nursing care plans - Comer, Sheree (Clifton Park, New York : Thomson/Delmar Learning, 2005)
"Delmar's Critical Care Nursing Care Plans, Second Edition, provides detailed information for nurses who care for patients in the critical care unit. All the information needed to develop specific and effective nursing care plans for the most commonly seen disorders is included. Each care plan presents information to guide users in developing comprehensive, individualized nursing care plans based on solid, scientific understanding of the condition and how it affects each of the patient's body systems. Care plans solicit specific patient data and prompt the user to individualize the interventions, consider cultural relevance, and evaluate the patient's individual responses."--Jacket
Cardiovascular system -- Respiratory system -- Neurologic system -- Gastrointestinal/hepatic system -- Hematologic system -- Renal/endocrine systems -- Musculoskeletal system -- Integumentary system -- Other
Includes bibliographical references and index.
Keywords: CRITICAL CARE